Development of speed and strength abilities of children aged 12-13 years in physical education classes in the COVID-19 pandemic - Olena Nesen (Pedagogy of Health)
Prerequisites and purpose of education. The COVID-19 pandemic has created unusual conditions for physical education teachers to work with schoolchildren. Children are forced to spend some time at home, which reduces the time for physical activity. The aim of the work is to track changes in the indicators of speed and strength abilities of children aged 12-13 years during the year in the conditions of mixed and distance learning.